“Boko Haram” Insulgence and the Threat to Education and Sustainable Development in Northern Nigeria - Akpotu, Nelson Ejiro (International Journal For Research In Educational Studies, 2019)
“Boko Haram” an Hausa name which literarily means “western education is sinful, sacrilege and forbidden” has been an Islamic jihadist militant group operating in most parts of Northern Nigeria that is predominantly Muslim settlement. Since 2009 when the aggressive violence started, over 4,000 people have been killed in the Northern states of Adamawa, Bauchi, Borno, Kaduna, Kano and Yobe including Abuja. In Borno State alone, since the beginning of 2012, at least 15,000 students have been forced out of schools and over 100 teachers and 100 students killed or wounded due to attacks on educational institutions by Boko Haram groups. Also, over 825 blocks of classrooms have been destroyed; fifty of the 175 primary schools in Borno State have been burnt or destroyed and 209 schools in Yobe State destroyed. The United Nations High Commission for Refugees (UNHCR) said about 10,000 Nigerians mostly children; women and elderly have fled to neighbouring countries like Cameroun, Niger and Chad. Records show that Nigeria has the highest rate of out- of- school children, numbering about 10.5 million; many of whom are found in the Northern States that is generally regarded as educationally backward. The insurgence of Boko Haram poses further challenges and threats to education. This forms the basis for this paper which tries to examine the consequences of Boko Haram insurgency on school enrolment and attendance of students and teachers; the provision of basic infrastructures for teaching and learning in the educationally backward states of Northern Nigeria It suggests the application of the human rights-based approach to the planning and implementation of the Nigerian education for sustainable socio- political and economic development.